Structure and Protein–Protein Interactions of Human UDP-Glucuronosyltransferases - Fujiwara, Ryoichi; Yokoi, Tsuyoshi; Nakajima, Miki (Frontiers in Pharmacology, 2016)
Mammalian UDP-glucuronosyltransferases (UGTs) catalyze the transfer of glucuronic acid from UDP-glucuronic acid to various xenobiotics and endobiotics. Since UGTs comprise rate-limiting enzymes for metabolism of various compounds, co-administration of UGT-inhibiting drugs and genetic deficiency of UGT genes can cause an increased blood concentration of these compounds. During the last few decades, extensive efforts have been made to advance the understanding of gene structure, function, substrate specificity, and inhibition/induction properties of UGTs. However, molecular mechanisms and physiological importance of the oligomerization and protein-protein interactions of UGTs are still largely unknown. While three-dimensional structures of human UGTs can be useful to reveal the details of oligomerization and protein-protein interactions of UGTs, little is known about the protein structures of human UGTs due to the difficulty in solving crystal structures of membrane-bound proteins. Meanwhile, soluble forms of plant and bacterial UGTs as well as a partial domain of human UGT2B7 have been crystalized and enabled us to predict three-dimensional structures of human UGTs using a homology-modeling technique. The homology-modeled structures of human UGTs do not only provide the detailed information about substrate binding or substrate specificity in human UGTs, but also contribute with unique knowledge on oligomerization and protein-protein interactions of UGTs. Furthermore, various in vitro approaches indicate that UGT-mediated glucuronidation is involved in cell death, apoptosis, and oxidative stress as well. In the present review article, recent understandings of UGT protein structures as well as physiological importance of the oligomerization and protein-protein interactions of human UGTs are discussed.